Discovery of Arabidopsis UGT73C1 as a steviol-catalyzing UDP-glycosyltransferase with chemical probes. Issue 52 (12th June 2018) - Zhou, Yiqing; Li, Weichao; You, Wenjing; Di, Zhengao; Wang, Mingli; Zhou, Haiyan; Yuan, Shuguang; Wong, Nai-Kei; Xiao, Youli
Abstract : A strategy for rapidly mining biological parts from plants for synthetic biology utilizing natural product-derived chemical probes has been reported. Abstract : Chemoselective and affinity-based probes of steviol were applied to the discovery of glycosyltransferase activity and corresponding UDP-glycosyltransferase in Arabidopsis thaliana, which illustrates a simple strategy for rapidly harnessing minable novel biological parts from plants for synthetic biology.